Paradiso - Lezama Lima, José 1910-1976 (Letras hispánicas, 2008)
This work, José Lezama Lima's only novel, discusses a homosexual's view of politics, religion, love, etc. after being exiled by Cuba's Castro-led government for discussing homosexuality - a taboo topic in Cuba.